External Capital Resources and Export Diversification in Developing Countries - Saleem, Ramsha; Chin Hong, Puah (International Journal of Economics and Financial Issues, 2025)
Developing countries have been trying to diversify their exports baskets since 1990s. Particularly, these countries are striving for export diversification through external capital resources inflow in the economy. This study attempts to explore the impact of external capital resources i.e. foreign direct investment inflow, remittances received, foreign aid and total external debt on export diversification. Moreover, this study utilizes a balanced panel of sixty five developing countries over the period 1995-2021 by employing a newly developed panel data estimation method, cross sectional Auto Regressive Distributed Lag (CS-ARDL). The robustness is checked by another novel estimation technique i.e. Method of Moments Quantile Regression (MMQR). The estimation methods are expounding heterogeneity and endogeniety. Empirical examination for four forms of foreign capital inflows do provide varying degree of significant contribution for increasing export diversification. Three capital resources are significant contributors whereby one of these resources are warranting export concentration. Further, these findings suggest that optimal inflow of external capital can be useful for sample countries and their productive use of external capital resources can serve as crucial channel to affect export diversification.